Writing successful reports and dissertations - Becker, Lucinda M., 1963- (Los Angeles : Sage, 2015)
"Help is here! In this handy little book you will find expert guidance to enable you to produce a successful report or dissertation. With a focus on developing an effective writing style and argument, this book will show you, step-by-step, how to plan and deliver a perfect piece of writing to gain top marks."--Page [4] of cover.
chapter 1. Why a dissertation? -- chapter 2. What is distinctive about a dissertation? -- chapter 3. What are research questions? -- chapter 4. What makes a good dissertation? -- chapter 5. When and why would I write a report? -- chapter 6. What is distinctive about a report? -- chapter 7. Should I be asking research questions in a report? -- chapter 8. Devising a strategy -- chapter 9. Gathering material -- chapter 10. Finding your voice -- chapter 11. Are you a natural planner? -- chapter 12. A planning strategy -- chapter 13. Your first step -- chapter 14. Four planning methods -- chapter 15. Negative pauses -- chapter 16. Necessary pauses -- chapter 17. Positive pauses -- chapter 18. Words -- chapter 19. Phrases -- chapter 20. Sentences -- chapter 21. Paragraphs -- chapter 22. Sections and chapters -- chapter 23. Increasing impact -- chapter 24. Checking your document -- chapter 25. Now take your fingers off the keyboard ...
Includes index.
Description based on MARC record for print version.
Keywords: elektronické knihy; electronic books; Dissertations, Academic; Report writing; Dissertations, Academic; Report writing